The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.3677188
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical cage behaviour and hydrogen migration in hydrogen and hydrogen-tetrahydrofuran clathrate hydrates

Abstract: Classical equilibrium molecular dynamics simulations have been performed to investigate dynamical properties of cage radial breathing modes and intra- and inter-cage hydrogen migration in both pure hydrogen and mixed hydrogen–tetrahydrofuran sII hydrates at 0.05 kbar and up to 250 K. For the mixed H2–THF system in which there is single H2 occupation of the small cage (labelled “1SC 1LC”), we find that no H2 migration occurs, and this is also the case for pure H2 hydrate with single small-cavity occupation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
(61 reference statements)
0
36
0
Order By: Relevance
“…Inter-cage migration has been observed by Gorman et al [21], as shown by Figure 2 of that article [21], as well as by Frankcombe and Kroes [20]. In ref.…”
Section: Mathematical Modellingmentioning
confidence: 62%
See 4 more Smart Citations
“…Inter-cage migration has been observed by Gorman et al [21], as shown by Figure 2 of that article [21], as well as by Frankcombe and Kroes [20]. In ref.…”
Section: Mathematical Modellingmentioning
confidence: 62%
“…In the latter case there was no migration detected for the hydrogen molecules (See Figure 5). The single hydrogen molecule in the small cages in both systems 1S1L and 1S4L are largely non-percolating (as also observed in [21]). More vigorous vibration of the large cages due to quadruple occupation in the case of 1S4L, particularly at higher temperatures, coupled with single-occupation of the small cages allows for limited hopping to occur between small and large cages.…”
Section: Gorman Et Al Have Studied the Energetics And Dynamical Propmentioning
confidence: 69%
See 3 more Smart Citations